(untitled) (Research, Society and Development, 2022)
Objective: To classify the adherence of outpatients living with the human immunodeficiency virus (HIV), as well as to describe the socioeconomic data and the factors that interfere or not with the pharmacotherapy. Methodology: Quantitative, descriptive and cross-sectional study carried out from the application of the instrument adapted from Delgado and Lima (2001) to classify adherence and to collect personal data and investigate factors associated with adherence, adapted forms from Reis (2014) were used. consisted of outpatients who use antiretroviral drugs in the specialized care service (SAE) of the João de Barros Barreto University Hospital (HUJBB) in Belém do Pará. Results/discussion: The results showed that regularity in consultations is closely linked to the adherence, which in turn is directly related to patients’ viral load. Social factors such as schooling and income are also important aspects in choosing to adhere to ART. Conclusion: Most of the interviewed patients are adherent to the pharmacological treatment. On the other hand, young patients with low education, married and living in urban areas with a shorter time of diagnosis were more likely to not adhere to ART, indicating a need for greater attention by the health team.